Polyolefin composition comprising polypropylene polymer and recycled plastic material

By extruding a blend of heterophase polypropylene copolymer and recycled plastic material in the presence of peroxide, polyolefin compositions with high impact strength, good melt flowability and high tensile modulus are solved. There is a problem of poor quality of recycled materials, which has achieved high-end market applications that compete with native materials.

CN119487119APending Publication Date: 2025-02-18BOREALIS AG
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202380051481.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-04
Filing Date
2023-07-03
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The poor quality of existing recycled polypropylene and polyethylene materials has resulted in limited applications in high-end markets and is difficult to compete with native materials.

Method used

Polyolefin compositions with high impact strength, good melt flowability and high tensile modulus are prepared by extruding a blend of a heterophase polypropylene copolymer with a recycled plastic material in the presence of peroxide.

Benefits of technology

The high performance of polyolefin compositions is achieved, able to meet the needs of the high-end market, and compete with native materials in mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005224979050000231
    Figure BDA0005224979050000231
Patent Text Reader

Abstract

The present invention relates to a polyolefin composition comprising: a) 35% to 65% by weight (based on the total weight of the polyolefin composition) of at least one heterophasic polypropylene copolymer, the at least one heterophasic polypropylene copolymer having a total ethylene C2 content of from 6 to 15 wt%, an ethylene content C2 (SF) content of the soluble fraction of from 25 to 40 wt%, and a melt flow rate MFR2 (230 DEG C, 2.16 kg, measured according to ISO 1133) in the range of from 60 g / 10 minutes to 90 g / 10 minutes, and wherein the at least one heterophasic polypropylene copolymer has a total ethylene C2 content of from 6 to 15 wt%, an ethylene content C2 (SF) content of the soluble fraction of from 25 to 40 wt%, and a melt flow rate MFR2 (230 DEG C, 2.16 kg, measured according to ISO 1133); and b) 35% to 65% by weight (based on the total weight of the polyolefin composition) of a blend of recycled plastic materials comprising polypropylene and polyethylene in a ratio of 3: 7 to 49.5: 1, said blend of recycled plastic materials being recycled from waste plastic materials derived from post consumer waste and / or post industrial waste, c) optionally further additives, wherein the sum of all the ingredients is always 100% by weight in total, and wherein the polyolefin composition has an impact strength (ISO 179-1, Charpy 1 eA + 23 DEG C) of 5 kJ / m2 to 8 kJ / m2, a melt flow rate MFR2 (230 DEG C, 2.16 kg, measured according to ISO 1133) of 30 g / 10 minutes to 80 g / 10 minutes, and a tensile modulus (Iso 527-2) in the range of 1450 MPa to 1600 MPa.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention relates to a polyolefin composition comprising at least one heterophasic polypropylene copolymer and recycled plastic material, to articles comprising said polyolefin composition and to a process for the preparation of such a polyolefin composition.

[0002] describe

[0003] Polyolefins, especially polyethylene and polypropylene, are increasingly consumed in large quantities in a wide range of applications, including packaging for food and other items, fibers, automotive components and a wide variety of manufactured goods. Considering the huge amount of waste collected compared to the amount of waste recycled back into the stream, there is still great potential for the intelligent reuse of plastic waste streams and the mechanical recycling of plastic waste.

[0004] A major trend in the field of polyolefins is the use of recycled materials from a variety of sources. Durable goods streams such as those from yellow bags, yellow bins, community collections, waste electrical equipment (WEE) or end-of-life vehicles (ELV) contain a variety of plastics. These materials can be processed to recycle acrylonitrile-butadiene-styrene (ABS), high impact polystyrene (HIPS), polypropylene (PP) and polyethylene (PE) plastics. Density separation in water can be used and then further separated based on fluorescence, near-infrared absorption or Raman fluorescence for separation. However, it is usually difficult to obtain pure recycled polypropylene or pure recycled polyethylene.

[0005] Typically, a large amount of polypropylene recycled on the market is a mixture of polypropylene (PP) and polyethylene (PE), which is especially true for post-consumer waste streams. In addition, commercial recyclates from post-consumer waste sources are routinely cross-contaminated with non-polyolefin materials (e.g., polyethylene terephthalate, polyamide, polystyrene) or non-polymer substances (such as wood, paper, glass or aluminum). These cross-contaminations greatly limit the final application of the recycling stream, leaving no useful final use. Polyolefin recycling materials, especially polyolefin recycling materials from post-consumer waste streams, are a mixture of PE and PP. The better the quality of the recycling material, the less available it is, and the more expensive it is.

[0006] The quality issues of recyclates compared to virgin can be overcome to some extent by blending recyclates with virgin polymers.

[0007] Compositions comprising virgin polymers (ie polymers used for the first time) and recycled mixed plastics were studied.

[0008] EP 0 575 465 B1 covers a polymer blend composition comprising: (a) 30 to 70 wt% of a low melting polymer comprising an ethylene / α-olefin copolymer, the low melting polymer having a molecular weight of 0.88 g / cm 3 Up to 0.915g / cm 3 %, an MFR of 1.5 dg / min to 7.5 dg / min, a molecular weight distribution of no more than 3.5, a composition distribution breadth index of greater than 70%, and a substantially single melting point in the range of 60°C to 115°C as measured as the DSC peak Tm; and (b) 70 wt% to 30 wt% of a propylene-based polymer having 88 mol% to 100 mol% propylene and 12 mol% to 0 mol% of an α-olefin other than propylene.

[0009] US 5,266,392 A claims a polyethylene / polypropylene blend comprising: ≥50 wt% crystalline polypropylene; at least about 10 wt% linear low density polyethylene having a density of about 0.915 to about 0.94 dispersed in a matrix of the polypropylene; and an amount of an ethylene / α-olefin plastomer compatibilizer having an α-olefin content of about 5 mol% to about 25 mol%, a melt index of greater than about 50 dg / min, a weight average molecular weight of about 5000 to about 50000, and a molecular weight of about 0.88 g / cm 3 About 0.90g / cm 3 density and at least 10% X-ray crystallinity. This covers the use of plastomers as compatibilizers in a very general way, including of course recycling. For plastomers only very low and very high densities are excluded, but pure HDPE is also excluded.

[0010] WO 2015 / 169690 A1 relates to a polypropylene-polyethylene blend comprising: (A) 75 to 90 wt% of a blend of (A-1) and (A-2): (A-1) 30 to 70 wt% of polypropylene, (A-2) 70 to 30 wt% of polyethylene; and (B) 10 to 25 wt% of a compatibilizer which is a heterophasic polyolefin composition, the heterophasic polyolefin composition comprising (B-1) 55 to 90 wt% of a polyolefin having an MFR2 of 1.0 to 300 g / 10 min (based on the formula (A)). % at 230° C. under 2.16 kg load according to ISO 1133) and (B-2) 45 wt. % to 10 wt. % of a copolymer of ethylene and propylene or a C4 to C10 alpha olefin, said copolymer having a glass transition temperature Tg (measured with DMTA) below −25° C. and an intrinsic viscosity (measured in decalin at 135° C.) of at least 3.0 dl / g, wherein the blend has (i) a Charpy notched impact strength (measured with ISO 1133) of at least 2% higher than that of the same blend without the compatibilizer (B); 179-1eA, measured at 23°C), and at the same time, (ii) a flexural modulus (according to ISO 178) that is at least 3% higher than that of the same blend without compatibilizer (B), and additionally (iii) a heat deformation resistance (determined using DMTA) represented by the temperature at which a storage modulus G' of 40 MPa is reached (T(G'=40 MPa)) that is at least 4°C higher than that of the same blend without compatibilizer (B).

[0011] EP 3 165 473 A1 relates to a polyolefin composition comprising: a blend (A) of recycled polypropylene and recycled polyethylene, a polypropylene having an MFR of not less than 50 g / 10 min, and a compatibilizer which is a heterophasic polyolefin composition, wherein the MFR of the entire composition is higher than 25 g / 10 min.

[0012] WO 2020 / 070176 A1 relates to a polyolefin composition comprising recycled polyolefin and suitable for use in higher value products. The composition comprises a propylene homopolymer having an MFR of at least 400 g / 10 min.

[0013] WO 2021 / 032458 A1 and WO 2021 / 144404 A1 disclose polypropylene-polyethylene blends comprising component A) being a recycle blend and component B) being a virgin heterophasic polypropylene copolymer). However, polypropylene-polyethylene blends have rather low tensile modulus and / or melt flow rate, making them unsuitable for certain applications.

[0014] However, known polymer compositions comprising recycled materials are not suitable for high-end markets, instead currently available recyclate compositions target low-end applications such as crates, plant pots, workbenches, etc. Due to their mechanical properties, currently available recyclate compositions cannot compete with virgin materials.

[0015] In order to serve high-end markets such as high-flow applications and to compete with virgin materials (especially in the non-food and non-health care product sectors), certain adjustments are needed. The main problems with currently available recyclates are composition (e.g. fluctuations in PP and PE content), consistency (in terms of flow properties), property profile (poor hardness-impact balance) and cross-contamination (e.g. non-polyolefin components, inorganic materials such as aluminum or paper), but also problems with color and odor.

[0016] Therefore, an object of the present invention is to provide a polyolefin composition comprising a polyolefin material recycled from waste plastic materials which does not have the disadvantages of polymer compositions according to the prior art. In particular, composite solutions combining virgin materials with recyclates are urgently needed to balance the above-mentioned issues and provide advanced material products to the market.

[0017] This object is solved by providing a polyolefin composition comprising:

[0018] a) 35 to 65 wt.-% (based on the total weight of the polyolefin composition) of at least one heterophasic polypropylene copolymer having a total ethylene C2 content of 6 to 15 wt.-%, an ethylene content of the soluble fraction C2 (SF) of 25 to 40 wt.-% and a melt flow rate MFR2 (230°C, 2.16 kg, measured according to ISO 1133) in the range of 60 to 90 g / 10 min; and

[0019] b) 35 to 65 wt.-% (based on the total weight of the polyolefin composition) of a blend of recycled plastic material comprising polypropylene and polyethylene in a ratio of 3:7 to 49.5:1, said blend of recycled plastic material being recycled from waste plastic material originating from post-consumer waste and / or post-industrial waste,

[0020] c) optionally further additives, wherein the sum of all constituents always amounts to 100 wt. %, wherein the polyolefin composition has

[0021] 5kJ / m 2 Up to 8kJ / m 2 Impact strength (ISO179-1, Charpy 1eA+23℃),

[0022] a melt flow rate MFR2 (230° C., 2.16 kg, measured according to ISO 1133) of 30 g / 10 min to 80 g / 10 min, and

[0023] Tensile modulus in the range of 1450 MPa to 1600 MPa (Iso 527-2).

[0024] As discussed in further detail below, polyolefin compositions according to the present invention are obtained by extruding the blend of at least one heterophasic polypropylene copolymer and recycled plastic material in the presence of at least one peroxide. Unexpectedly, by doing so, a polyolefin composition combining high impact strength with good MFR and high tensile modulus has been obtained. Although polyolefin compositions of the present invention are obtained in the presence of at least one peroxide during extrusion, polyolefin compositions of the present invention are (almost) free of peroxide; That is, only trace amounts of hydrogen peroxide, if any, can be detected.

[0025] The polyolefin compositions of the present invention combine both recycled materials that meet recycling quotes and help reduce waste and virgin materials that compensate for variation / composition issues in recyclates. Consumer demands can be met by providing a polyolefin composition that combines high impact modulus, melt flow and tensile modulus.

[0026] The polyolefin composition of the present invention combines virgin high flow heterophasic polypropylene material as an impact reinforcement for recycled PP / PE material. This allows the polyolefin composition with a large amount of recycled material to be used in current applications in the field of covers and closures and packaging (e.g. lids), especially thin wall packaging applications.

[0027] It should be understood that polyolefin compositions of the present invention do not include talc (except the amount present in the recyclate), glass fiber, rubber or any other solid material.It should also be understood that polyolefin compositions of the present invention preferably do not contain or include any virgin polypropylene homopolymer, except as a heterophasic polypropylene copolymer matrix and as a dosing agent.

[0028] For the purposes of this specification and the appended claims, the term "recycled" is used to indicate that the material is recovered from post-consumer waste and / or post-industrial waste. That is, post-consumer waste refers to an object that has completed at least the first use cycle (or life cycle), that is, has experienced its first purpose and has passed through the hands of a consumer; while post-industrial waste refers to manufacturing waste that does not usually reach a consumer. In the subject matter of the present invention, "recycled polymer" may also contain up to 17% by weight, preferably up to 3% by weight, more preferably up to 1% by weight, and even more preferably up to 0.1% by weight of other components derived from the first use, based on the total weight of the recycled polymer. The type and amount of these components affect the physical properties of the recycled polymer. The physical properties given below relate to the main components of the recycled polymer.

[0029] As further described below, typical other components derived from the first use are thermoplastic polymers (such as polystyrene and PA6), talc, chalk, ink, wood, paper, limonene and fatty acids. The content of polystyrene (PS) and polyamide 6 (PA6) in the recycled polymer can be determined by Fourier Transform Infrared Spectroscopy (FTIR), and the content of talc, chalk, wood and paper can be measured by Thermogravimetric Analysis (TGA).

[0030] The term "virgin" refers to newly produced materials and / or objects prior to first use and not recycled. A polymer is a "virgin" polymer when the source of the polymer is not explicitly mentioned.

[0031] The total amount of virgin heterophasic polypropylene polymer used in the polyolefin composition of the present invention may add up to a range of 40 to 60 wt%, preferably 45 to 55 wt%, more preferably 48 to 52 wt% (based on the total weight of the polymer composition).

[0032] The amount of the blend of recycled plastic material comprising polypropylene and polyethylene in a ratio of 3:7 to 49.5:1, preferably 3:7 to 12:1 used in the polyolefin composition of the present invention, which is recycled from waste plastic material originating from post-consumer waste and / or post-industrial waste, may be in the range of 40 to 60 wt.-%, preferably 45 to 55 wt.-%, more preferably 48 to 52 wt.-% (based on the total weight of the polymer composition).

[0033] It should be understood that the amount of the blend of heterophasic propylene copolymer (PPHECO) and recycled material is always complementary to each other. For example, in one embodiment, the composition can include 60 wt% heterophasic propylene copolymer (PPHECO) and 40 wt% polypropylene recycled material, or 55 wt% heterophasic propylene copolymer (PPHECO) and 45 wt% polypropylene recycled material, or 50 wt% heterophasic propylene copolymer (PPHECO) and 50 wt% polypropylene recycled material, or any intermediate range.

[0034] In a preferred embodiment, the polyolefin composition of the present invention may comprise:

[0035] - 70 wt.% heterophasic propylene copolymer (PPHECO) and 30 wt.% polypropylene regrind;

[0036] - 65 wt.% heterophasic propylene copolymer (PPHECO) and 35 wt.% polypropylene regrind;

[0037] - 60 wt.% heterophasic propylene copolymer (PPHECO) and 40 wt.% polypropylene regrind;

[0038] - 55 wt.% heterophasic propylene copolymer (PPHECO) and 45 wt.% polypropylene regrind;

[0039] - 50 wt.% heterophasic propylene copolymer (PPHECO) and 50 wt.% polypropylene recycle.

[0040] The impact strength (ISO179, Charpy 1eA+23°C) of the polymer composition according to the present invention is 5 kJ / m 2 Up to 8kJ / m 2 , more specifically 5.2 kJ / m 2 Up to 7.5 kJ / m 2 , even more specifically 5.5 kJ / m 2 Up to 7 kJ / m 2 , and most specifically 5.8 kJ / m 2 Up to 6.5 kJ / m 2 within the range.

[0041] In one embodiment, the polyolefin composition of the present invention is also characterized by a melt flow rate MFR2 (230°C, 2.16 kg, measured according to ISO 1133-1) in the range of 30 g / 10 min to 80 g / 10 min, preferably 30 g / 10 min to 75 g / 10 min, more preferably 35 g / 10 min to 70 g / 10 min, or 30 g / 10 min to 36 g / 10 min.

[0042] In another embodiment, the polyolefin composition of the present invention is characterized by a tensile modulus (ISO 527-2) in the range of 1450 to 1600 MPa, more particularly 1450 to 1550 MPa, even more preferably 1450 to 1500 MPa, yet more preferably 1460 to 1500 MPa.

[0043] In one embodiment, the polyolefin composition of the present invention may have a 2 Up to 6.5 kJ / m 2 The composite has an impact strength of 1000 MPa to 2000 MPa, a melt flow rate MFR2 of 30 to 36 g / 10 min, and a tensile modulus of 1455 to 1500 MPa.

[0044] Heterophasic Polypropylene Virgin Polymer (PPHeco)

[0045] The heterophasic polypropylene copolymer comprises a polypropylene matrix (M) and an elastomeric copolymer (E) as polymer components. The polypropylene matrix (M) is preferably a random propylene copolymer or a propylene homopolymer, the latter being particularly preferred. The elastomeric copolymer (E) comprises units derived from propylene and ethylene and / or C4 to C20 α-olefins, more preferably derived from ethylene and / or C4 to C10 α-olefins, most preferably derived from ethylene, C4 α-olefins, C6 α-olefins and / or C8 α-olefins (e.g. ethylene), and optionally units derived from conjugated dienes.

[0046] The at least one heterophasic polypropylene copolymer may have a melt flow rate MFR2 (230°C, 2.16 kg, measured according to ISO 1133) in the range of 60 to 90 g / 10 min, preferably 650 to 90 g / 10 min, more preferably 70 to 90 g / 10 min, even more preferably 70 to 85 g / 10 min.

[0047] The at least one heterophasic polypropylene polymer used as primary polymer in the polyolefin composition of the present invention is:

[0048] at least one heterophasic polypropylene copolymer (PPHeco-1) having a melt flow rate MFR2 (230°C, 2.16 kg, measured according to ISO 1133) in the range of 60 to 90 g / 10 min, preferably 70 to 90 g / 10 min, more preferably 72 to 88 g / 10 min;

[0049] At least one heterophasic polypropylene copolymer (PPHeco-2) having a melt flow rate MFR2 (230°C, 2.16 kg, measured according to ISO 1133) in the range of 65 to 80 g / 10 min, more preferably 65 to 75 g / 10 min; or a mixture thereof.

[0050] It is to be understood that the polyolefin composition of the present invention may comprise not only one heterophasic virgin polypropylene copolymer but two heterophasic virgin polypropylene copolymers having different melt flow rates. This allows adjusting the melt flow rate of the final polyolefin composition.

[0051] Heterophasic polypropylene copolymer (PPHeco-1):

[0052] The at least one heterophasic polypropylene copolymer (PPHeco-1) has a melt flow rate MFR2 (230°C, 2.16 kg, measured according to ISO 1133) in the range of 60 to 90 g / 10 min, preferably 70 to 90 g / 10 min, more preferably 72 to 88 g / 10 min.

[0053] The heterophasic polypropylene copolymer (PPHeco-1) of the instant invention has a content of soluble fraction (SF) determined according to CRYSTEX analysis in the range of 10.0 to 25.0 wt.-%, preferably in the range of 15.0 to 20.0 wt.-%, more preferably in the range of 16.0 to 18.0 wt.-%, based on the total weight of the heterophasic polypropylene copolymer.

[0054] The soluble fraction (SF) of the heterophasic polypropylene copolymer (PPHeco-1) is determined by 13 The ethylene content (C2(SF)) determined by quantitative FT-IR spectroscopy calibrated with C-NMR spectrum is in the range of 25.0 wt.% to 40.0 wt.%, preferably in the range of 25.0 wt.% to 35.0 wt.%, more preferably in the range of 30.0 wt.% to 32.0 wt.%.

[0055] The soluble fraction (SF) of the heterophasic polypropylene copolymer (PPHeco-1) has an intrinsic viscosity (iV(SF)) of not more than 3.5 dl / g, preferably not more than 2.5 dl / g, such as in the range of 1.0 to 3.5 dl / g, preferably in the range of 1.2 to 1.5 dl / g, such as 1.23 dl / g or 1.46 dl / g.

[0056] Heterophasic polypropylene copolymer (PPHeco-1) is prepared by 13The total ethylene (C2) content, determined by quantitative FT-IR spectroscopy calibrated by C-NMR spectrum, is preferably from 6.0 to 15.0 wt.-%, more preferably from 6 to 10.0 wt.-%, most preferably from 6.0 to 8.0 wt.-%.

[0057] The heterophasic polypropylene copolymer (PPHeco-1) may have a Charpy notched impact strength (NIS) measured according to ISO 179-1eA at 23°C of at least 4 kJ / m 2 , preferably at least 5 kJ / m 2 , for example at 4 kJ / m 2 Up to 7 kJ / m 2 In the range of 4 kJ / m 2 Up to 6kJ / m 2 In the range of, for example, 4 kJ / m 2 or 5 kJ / m 2 The heterophasic polypropylene copolymer (PPHeco-1) may have a tensile modulus measured according to ISO 178 of at least 1000 MPa, preferably at least 1400 MPa, such as in the range of 1000 to 2000 MPa, preferably in the range of 1200 to 1800 MPa, such as 1300 MPa.

[0058] Heterophasic polypropylene copolymer (PPHeco-1) is known in the art and commercially available from eg Borealis AG.

[0059] Heterophasic polypropylene copolymer (PPHeco-2):

[0060] The at least one heterophasic polypropylene copolymer (PPHeco-2) has a melt flow rate MFR2 (230°C, 2.16 kg, measured according to ISO 1133) in the range of 60 to 90 g / 10 min, more preferably 65 to 80 g / 10 min, e.g. 65 to 75 g / 10 min.

[0061] The instant heterophasic polypropylene copolymer (PPHeco-2) has a content of soluble fraction (SF) determined according to CRYSTEX analysis in the range of 10.0 to 20.0 wt.-%, preferably 15.0 to 18.0 wt.-%, based on the total weight of the heterophasic polypropylene copolymer.

[0062] The soluble fraction (SF) of the heterophasic polypropylene copolymer (PPHeco-2) is determined by 13The ethylene content (C2(SF)) determined by quantitative FT-IR spectroscopy calibrated with the C-NMR spectrum is in the range of 25.0 wt.-% to 40.0 wt.-%, preferably in the range of 25.0 wt.-% to 35.0 wt.-%, more preferably in the range of 25.0 wt.-% to 30.0 wt.-%.

[0063] The soluble fraction (SF) of the heterophasic polypropylene copolymer (PPHeco-2) has an intrinsic viscosity (iV(SF)) of not more than 4.5 dl / g, preferably not more than 3.5 dl / g, such as in the range of 2.0 to 4.5 dl / g, preferably in the range of 2.5 to 3.5 dl / g, more preferably in the range of 2.5 to 3.0 dl / g, such as in the range of 2.6 to 2.7 dl / g.

[0064] Heterophasic polypropylene copolymer (PPHeco-2) is prepared by 13 The total ethylene (C2) content, as determined by quantitative FT-IR spectroscopy calibrated with the C-NMR spectrum, is from 6.0 to 15.0 wt.%, more preferably from 6 to 10.0 wt.%, most preferably from 6.0 to 8.0 wt.%.

[0065] The heterophasic polypropylene copolymer (PPHeco-2) may have a Charpy notched impact strength (NIS) measured according to ISO 179-1eA at 23°C of at least 4 kJ / m 2 , preferably at least 5 kJ / m 2 , for example at 4 kJ / m 2 Up to 7 kJ / m 2 In the range of 5 kJ / m 2 Up to 6kJ / m 2 In the range of, for example, 5 kJ / m 2 The heterophasic polypropylene copolymer (PPHeco-2) may have a tensile modulus measured according to ISO 178 of at least 1000 MPa, preferably at least 1400 MPa, such as in the range of 1000 to 2000 MPa, preferably in the range of 1300 to 1800 MPa, such as 1500 MPa.

[0066] Heterophasic polypropylene copolymer (PPHeco-2) is known in the art and commercially available from eg Borealis AG.

[0067] Blends of recycled materials

[0068] The blend is obtained from a recycled waste stream. The blend may be either recycled post-consumer waste or post-industrial waste, for example from the automotive industry, or alternatively a combination of the two. It is particularly preferred that the blend consists of recycled post-consumer waste and / or post-industrial waste.

[0069] In one aspect, the blend can be a polypropylene (PP)-rich material for recycling plastic materials, and the polypropylene (PP)-rich material includes significantly more polypropylene than polyethylene. The recycled waste stream with more polypropylene can be obtained, for example, from the automotive industry, especially because some automotive parts such as bumpers are the source of quite pure polypropylene materials in the recycling stream, or obtained by enhanced sorting. When sorted accordingly, rich PP recyclates can also be obtained from yellow bag raw materials. Rich PP materials can be obtained by selective treatment, degassing and filtering, and / or by separation according to type and color (such as NIR or Raman sorting and VIS sorting). It can be obtained from a life waste stream (that is, it is a product of life recycling), such as the "yellow bag" recycling system organized by the "Green Dot" organization running in some areas of Germany.

[0070] Preferably, the polypropylene-rich recycled material is obtained from recycled waste by a plastic recycling process known in the art. Such PP-rich recycled materials are commercially available from, for example, Corepla (Italian Consortium for the collection, recovery, recycling of packaging plastic wastes), Resource Plastics Corp. (Brampton, Ontario), Kruschitz GmbH, Plastics and Recycling (Austria), Vogt Plastik GmbH (Germany), Mtm ​​Plastics GmbH (Germany), etc. Non-exhaustive examples of polypropylene-rich recycled materials include: PP, PP (MtmPlastics GmbH), MOPRYLENE PC B-420 white, MOPRYLENE PC B 440 (MorssinkhofPlastics, The Netherlands), SYSTALEN PP-C24000; Systalen PP-C44000; Systalen PP-C14901, Systalen PP-C17900, Systalen PP-C2400, Systalen 13704GR 015, Systalen 13404GR014, Systalen PP-C14900 GR000 (Der Grüne Punkt, Germany), Vision (Veolia) PPC BC2006HS or PP MONO.

[0071] It is believed that the present invention may be applicable to a wide range of recycled polypropylene materials or materials or compositions having a high content of recycled polypropylene.The polypropylene-rich recycled material may be in the form of pellets.

[0072] As mentioned above, the polyolefin composition according to the present invention comprises a polymer blend as a blend, the polymer blend comprising polypropylene and polyethylene; wherein the weight ratio of polypropylene to polyethylene is 3:7 to 49.5:1, and wherein the polymer blend is a recycled material.

[0073] Yet another preferred embodiment of the invention provides that the ratio of polypropylene to polyethylene is from 7: 1 to 40: 1, and preferably from 10: 1 to 30: 1. The weight ratio of polypropylene to polyethylene is preferably from 19: 1 to 7:3.

[0074] According to one embodiment, the blend of recycled plastic materials comprises the following relative amount of units derived from propylene relative to the total weight of the composition of the blend: greater than 50 wt.-%, preferably greater than 53 wt.-%, more preferably greater than 60 wt.-%, more preferably greater than 70 wt.-%, more preferably greater than 75 wt.-%, more preferably greater than 80 wt.-%, yet more preferably greater than 90 wt.-% and even more preferably greater than 95 wt.-%.

[0075] Another preferred embodiment of the present invention provides that the content of polypropylene a1) in the blend is in the range of 75 wt % to 99 wt %, and preferably in the range of 83 wt % to 95 wt %, based on the total weight of the blend of recycled material. The content of polypropylene in the blend can be determined by FTIR spectroscopy as described in the experimental part. More preferably, the polypropylene component of the recycled material blend comprises more than 95 wt %, preferably 96 wt % to 99.9 wt % of isotactic polypropylene, and most preferably consists of isotactic polypropylene.

[0076] In addition, the blend can have the following relative amount of units derived from ethylene: less than 47% by weight, more preferably less than 40% by weight, more preferably less than 30% by weight, more preferably less than 20% by weight, and most preferably less than 10% by weight. The recyclate blend preferably includes units derived from ethylene in the following amount: 5.0% to 17.5% by weight, more preferably 6.0% to 15.0% by weight, and still more preferably 7.5% to 13.0% by weight. Typically, relative to the total weight of the blend, the relative amount of units derived from ethylene is greater than 5% by weight. It should be understood that the ethylene present is preferably ethylene derived from polyethylene and a copolymer comprising ethylene.

[0077] In another preferred embodiment of the invention, based on the total weight of the blend A), the content of polyethylene a2) in the blend is in the range of 1 wt % to 25 wt %, preferably in the range of 5 wt % to 20 wt %, and more preferably in the range of 7 wt % to 17 wt %. The content of polyethylene a2) in the blend can be determined by Crystex as described in the experimental part. More preferably, component a2) consists of polyethylene and a copolymer comprising ethylene.

[0078] The blend of recycled plastic materials is suitably characterized by CRYSTEX QC analysis. In the CRYSTEX QC analysis, a crystalline fraction (CF) and a soluble fraction (SF) are obtained which can be quantified and analyzed with respect to monomer and comonomer content and intrinsic viscosity (iV).

[0079] In CRYSTEX QC analysis, the blends of recycled plastic materials showed the following properties:

[0080] - a crystalline fraction (CF) content determined according to CRYSTEX QC analysis in the range of 82.5 to 96.0 wt.-%, preferably in the range of 84.0 to 95.5 wt.-%, more preferably in the range of 85.0 to 95.0 wt.-%, and

[0081] - the soluble fraction (SF) content determined according to CRYSTEX QC analysis is in the range of 4.0 to 17.5 wt.-%, preferably in the range of 4.5 to 16.0 wt.-%, more preferably in the range of 5.0 to 15.0 wt.-%.

[0082] The crystalline fraction (CF) has one or more, preferably all, of the following characteristics:

[0083] - As measured by quantitative 13The ethylene content (C2(CF)) determined by FT-IR spectroscopy calibrated with the C-NMR spectrum is in the range of 1.0 wt.-% to 12.5 wt.-%, preferably in the range of 1.5 wt.-% to 11.0 wt.-%, more preferably in the range of 2.0 wt.-% to 10.0 wt.-%; and / or

[0084] - the intrinsic viscosity (iV(CF)) as measured in decalin at 135° C. according to DIN ISO 1628 / 1 is preferably in the range of 1.0 dl / g to less than 2.6 dl / g, more preferably in the range of 1.2 dl / g to 2.5 dl / g, still more preferably in the range of 1.3 dl / g to 2.4 dl / g.

[0085] The soluble fraction (SF) has one or more, preferably all, of the following characteristics:

[0086] - As measured by quantitative 13 The ethylene content determined by FT-IR spectroscopy calibrated with a C-NMR spectrum (C2(SF)) is preferably in the range of 20.0 wt.-% to 55.0 wt.-%, preferably in the range of 22.0 wt.-% to 50.0 wt.-%, more preferably in the range of 24.0 wt.-% to 48.0 wt.-%; and / or

[0087] - the intrinsic viscosity (iV(SF)) as measured in decalin at 135° C. according to DIN ISO 1628 / 1 is in the range of 0.9 to 2.5 dl / g, preferably in the range of 1.0 to 2.3 dl / g, more preferably in the range of 1.1 to 2.2 dl / g.

[0088] The polyethylene fraction of the recycled material may include recycled high density polyethylene (rHDPE), recycled medium density polyethylene (rMDPE), recycled low density polyethylene (rLDPE), linear low density polyethylene (LLDPE), and mixtures thereof. In one embodiment, the recycled material has an average density greater than 0.8 g / cm 3 , preferably greater than 0.9 g / cm 3 , most preferably greater than 0.91 g / cm 3 High density PE.

[0089] The polyethylene fraction of the recycled material may also contain plastomers. Plastomers are polymer materials that combine rubber-like properties with the processing capabilities of plastics. Important plastomers are ethylene-alpha olefin copolymers.

[0090] Ethylene-based plastomers are preferably copolymers of ethylene and C4 to C8 alpha-olefins. Suitable C4 to C8 alpha-olefins include 1-butene, 1-hexene and 1-octene, preferably 1-butene or 1-octene, and more preferably 1-octene. Preferably, copolymers of ethylene and 1-octene are used. Such ethylene-based plastomers can be commercially available from Borealis AG (Austria) under the trade name Queo, commercially available from Dow Chemical Corp (U.S.) under the trade name Engage or Affinity, or commercially available from Mitsui under the trade name Tafmer. Alternatively, ethylene-based plastomers can be prepared by known methods in the presence of suitable catalysts known to those skilled in the art (such as vanadium oxide catalysts or single-site catalysts, such as metallocenes or restricted geometry catalysts) in one-stage or two-stage polymerization processes, the polymerization process including solution polymerization, slurry polymerization, gas phase polymerization or a combination thereof. It is possible that ethylene-based plastomers have been included in post-consumer waste and / or post-industrial waste for producing recycled blends. Alternatively, it is possible to add ethylene-based plastomers to post-consumer waste and / or post-industrial waste during the scrap plastic recycling process to produce a recyclate blend.

[0091] Another preferred embodiment of the present invention provides that the recyclate blend comprises less than 5 wt.-%, preferably less than 3 wt.-%, and more preferably 0.01 wt.-% to 2 wt.-% of thermoplastic polymers other than polypropylene and polyethylene, more preferably less than 4.0 wt.-% of PA6 and less than 5 wt.-% of polystyrene, still more preferably the blend comprises 0.5 wt.-% to 3 wt.-% of polystyrene, based on the total weight of the recyclate blend.

[0092] According to yet another preferred embodiment of the present invention, the recyclate blend comprises less than 5 wt%, preferably less than 4 wt%, and more preferably 0.01 wt% to 4 wt% talc, based on the total weight of the recyclate blend.

[0093] In another preferred embodiment of the present invention, the recyclate blend comprises less than 4 wt%, preferably less than 3 wt%, and more preferably 0.01 wt% to 2 wt% chalk, based on the total weight of the recyclate blend.

[0094] According to another preferred embodiment of the present invention, the recyclate blend comprises less than 1 wt. %, preferably less than 0.5 wt. %, and more preferably 0.01 wt. % to 1 wt. % of paper, based on the total weight of the recyclate blend.

[0095] Yet another preferred embodiment of the invention provides that the recyclate blend comprises less than 1 wt.-%, preferably less than 0.5 wt.-%, and more preferably 0.01 wt.-% to 1 wt.-% wood, based on the total weight of the recyclate blend.

[0096] In another preferred embodiment of the present invention, the recyclate blend comprises less than 1 wt%, preferably less than 0.5 wt%, and more preferably 0.01 wt% to 1 wt% of metals based on the total weight of the recyclate blend.

[0097] According to the present invention, the limonene content of the recyclate blend as determined using solid phase microextraction (HS-SPME-GC-MS) is 0.1 ppm to 100 ppm, more preferably 1 ppm to 50 ppm, most preferably 2 ppm to 35 ppm. Limonene is conventionally found in recycled polyolefin materials and is derived from packaging applications in the field of cosmetics, detergents, shampoos and similar products. Therefore, when the recyclate blend contains materials derived from such types of domestic waste streams, the recyclate blend contains limonene.

[0098] Fatty acid content is another index of the recovery source of recyclate blend. However, in some cases, due to the special treatment in the recovery process, fatty acid content may be lower than detection limit. According to the present invention, the fatty acid content of recyclate blend as determined using solid phase microextraction (HS-SPME-GC-MS) is preferably 1ppm to 200ppm, preferably 1ppm to 150ppm, more preferably 2ppm to 100ppm, most preferably 3ppm to 80ppm.

[0099] In a preferred aspect, the recyclate blend (i) comprises less than 5 wt%, preferably less than 1.5 wt% polystyrene; and / or (ii) comprises less than 3.5 wt%, preferably less than 1 wt% talc; and / or (iii) comprises less than 1.0 wt%, preferably less than 0.5 wt% polyamide.

[0100] The blend may also comprise, due to recycled origin, organic fillers and / or inorganic fillers and / or additives in an amount of up to 10% by weight, preferably 3% by weight, relative to the weight of the blend.

[0101] Thus, in one embodiment of the polyolefin composition of the present invention, the blend of recycled plastic materials comprises:

[0102] A-1) a polypropylene content of 50 to 99% by weight,

[0103] A-2) a polyethylene content of 1 to 40% by weight,

[0104] A-3) 0 to 5.0 wt. % of polystyrene and / or copolymers such as ABS,

[0105] A-4) 0 to 3.0% by weight of a stabilizer,

[0106] A-5) 0 to 4.0% by weight of polyamide-6,

[0107] A-6) 0 to 3.0% by weight of talc,

[0108] A-7) 0 to 3.0% by weight of chalk,

[0109] A-8) 0 to 1.0 wt. % of paper,

[0110] A-9) 0 to 1.0% by weight of wood,

[0111] A-10) 0 to 0.5% by weight of a metal,

[0112] A-11) 0.1 ppm to 100 ppm of limonene as determined by using solid phase microextraction (HS-SPME-GC-MS), and

[0113] A-12) a total fatty acid content of 0 ppm to 200 ppm as determined by using solid phase microextraction (HS-SPME-GC-MS),

[0114] All amounts are given relative to the total weight of the recyclate blend.

[0115] As noted above, the recyclate blend may include one or more additional components selected from the group consisting of:

[0116] A-4) up to 3.0% by weight of stabilizers, preferably up to 2.0% by weight of stabilizers, A-5) up to 4.0% by weight of polyamide-6, preferably up to 2.0% by weight of polyamide-6,

[0117] A-6) up to 3.0% by weight of talc, preferably up to 1.0% by weight of talc,

[0118] A-7) up to 3.0 wt. % chalk, preferably up to 1.0 wt. % chalk,

[0119] A-8) up to 1.0 wt. % paper, preferably up to 0.5 wt. % paper,

[0120] A-9) up to 1.0 wt. % wood, preferably up to 0.5 wt. % wood, and

[0121] A-10) up to 0.5% by weight of metal, preferably up to 0.1% by weight of metal.

[0122] In one embodiment, the melt flow rate MFR2 (230°C, 2.16 kg, measured according to ISO 1133) of the blend of recycled plastic materials comprising polypropylene and polyethylene is at least 5 g / 10 min, preferably at least 10 g / 10 min, more preferably at least 15 g / 10 min, in particular in the range of 5 g / 10 min to 50 g / 10 min, preferably 10 g / 10 min to 45 g / 10 min, more preferably 15 g / 10 min to 40 g / 10 min.

[0123] According to another embodiment, the melt flow rate MFR2 (ISO 1133, 230°C, 2.16 kg) of the blend of recycled plastic materials may be in the range of 15 to 50 g / 10 min, and preferably in the range of 18 to 36 g / 10 min.

[0124] In another preferred embodiment of the present invention, the Charpy notched impact strength of the recyclate blend measured at 23°C according to ISO 179-1eA is greater than 3.0 kJ / m 2 , preferably at 4.0 kJ / m 2 Up to 8.0kJ / m 2 and more preferably within the range of 5.0 kJ / m 2 Up to 6.0 kJ / m 2 within the range.

[0125] Another preferred embodiment of the invention provides that the tensile modulus of the recyclate blend, measured according to ISO 527-2, is in the range of 800 MPa to 1500 MPa and preferably in the range of 1100 MPa to 1400 MPa.

[0126] In one embodiment, the recyclate blend preferably has one or more, preferably all, of the following properties:

[0127] - melt flow rate MFR2 (230°C, 2.16 kg, ISO 1133) of 6.0 g / 10 min to 40 g / 10 min, preferably 8.0 g / 10 min to 40 g / 10 min, more preferably 9.0 g / 10 min to 36 g / 10 min; and / or

[0128] -Polydispersity index PI is 2.0Pa -1 To 5.0Pa -1 , preferably 2.2Pa -1 To 4.5Pa -1 , more preferably 2.5Pa-1 To 4.0Pa -1 ; and / or

[0129] Complex viscosity η at -0.05 rad / s 0.05 1000 kPa·sec to 5000 kPa·sec, preferably 1200 kPa·sec to 4500 kPa·sec, more preferably 1400 kPa·sec to 4000 kPa·sec; and / or

[0130] Complex viscosity η at -300 rad / s 300 100 kPa·sec to 500 kPa·sec, preferably 150 kPa·sec to 400 kPa·sec, more preferably 175 kPa·sec to 300 kPa·sec, and / or

[0131] -Density: 905kg / m 3 Up to 930kg / m 3 , preferably 910kg / m 3 Up to 925kg / m 3 , more preferably 913 kg / m 3 Up to 922kg / m 3 ; and / or

[0132] - limonene content as determined by using solid phase microextraction (HS-SPME-GC-MS): 0.1 ppm to 50 ppm; and / or

[0133] - a tensile modulus of 1000 MPa to 1500 MPa, preferably 1100 MPa to 1400 MPa; and / or

[0134] Charpy notched impact strength at -23°C (CNIS at 23°C) is 3.0 kJ / m 2 Up to 7.5 kJ / m 2 , preferably 4.0 kJ / m 2 Up to 7.0 kJ / m 2 .

[0135] The preferably used recyclate blend (blend B1) is available from mtm Plastics GmbH. Blend B1 is a post-consumer recyclate polypropylene based material having the following: 916 kg / m 3The present invention relates to a polyurethane foam having a density of 100 g / 100 g (determined in accordance with DIN EN ISO 1183), a melt flow rate of 36 g / 10 min (determined in accordance with DIN EN ISO 1133 at 230°C / 2.16 kg), a moisture content of less than 0.1% (determined via a moisture infrared analyzer at 105°C), a tensile modulus of greater than 1100 MPa (determined in accordance with DIN EN ISO 527 at 1 mm / min), a yield stress of greater than 24 MPa (determined in accordance with DIN EN ISO 527 at 50 mm / min) and a tensile strain of greater than 18% (determined in accordance with DIN EN ISO 527 at 50 mm / min).

[0136] Other recyclate blends that may be used are now described.

[0137] Blend B2:

[0138] Total C2 content 8 wt% to 9 wt%, C2 (CF) content 4 wt% to 5 wt%, C2 (SF) content 30 wt% to 34 wt%, MFR2 32 g / 10 min to 34 g / 10 min, tensile modulus 1300 MPa to 1400 MPa, impact strength (Charpy test 23 ° C) 5 KJ / m 2 Up to 6.5KJ / m 2 ;

[0139] Blend B3:

[0140] MFR2 18g / 10min to 19g / 10min, tensile modulus 1200MPa to 1300MPa, impact strength (Charpy test 23℃) 5KJ / m 2 Up to 6KJ / m 2 ;

[0141] Blend B4:

[0142] Total C2 content 9 wt% to 11 wt%, C2 (CF) content 7 wt% to 8 wt%, C2 (SF) content 32 wt% to 33 wt%, MFR2 24 g / 10 min to 25 g / 10 min, tensile modulus 1300 MPa to 1400 MPa, impact strength (Charpy test 23 ° C) 5 KJ / m 2 Up to 6KJ / m 2 ;

[0143] Blend B5:

[0144] Total C2 content 7 wt% to 9 wt%, C2 (CF) content 5 wt% to 7 wt%, C2 (SF) content 29 wt% to 34 wt%, MFR2 23 g / 10 min to 25 g / 10 min, tensile modulus 1100 MPa to 1300 MPa, impact strength (Charpy test 23 ° C) 4 KJ / m 2 Up to 5KJ / m 2 ;

[0145] Blend B6:

[0146] Total C2 content 7 wt% to 9 wt%, C2 (CF) content 5 wt% to 7.5 wt%, C2 (SF) content 27 wt% to 33 wt%, MFR2 15 g / 10 min to 17 g / 10 min, tensile modulus 1200 MPa to 1300 MPa, impact strength (Charpy test 23 ° C) 5 KJ / m 2 Up to 6KJ / m 2 .

[0147] Dosing agent:

[0148] In one embodiment, the polyolefin composition may include at least one dosing agent for accepting fillers / pigments during extrusion. The at least one dosing agent may have a melt flow rate MFR2 of 1 g / 10 min to 5 g / 10 min, preferably 2 g / 10 min to 3 g / 10 min and 800 kg / m 3 Up to 100kg / m 3 , preferably 900kg / m 3 Up to 950kg / m 3 Such polymers are commercially available from, for example, Borealis AG.

[0149] The amount of dosing agent in the polyolefin composition may be from 1 wt% to 2 wt%, such as from 1.2 wt% to 1.4 wt%.

[0150] Polymer composition

[0151] In the following, more specific embodiments of the polymer composition according to the present invention are described.

[0152] In a first embodiment, a polyolefin composition is provided comprising:

[0153] a) 35 to 65 wt.-% (based on the total weight of the polyolefin composition) of at least one heterophasic polypropylene copolymer (PPHECO-2) having a total ethylene C2 content of 6 to 15 wt.-%, an ethylene content of the soluble fraction C2 (SF) of 25 to 30 wt.-% and a melt flow rate MFR2 (230°C, 2.16 kg, measured according to ISO 1133) in the range of 65 to 80 g / 10 min, more preferably 65 to 75 g / 10 min,

[0154] b) 35 to 65 wt.-% (based on the total weight of the polyolefin composition) of a blend of recycled plastic material comprising polypropylene and polyethylene in a ratio of 3:7 to 49.5:1, said blend of recycled plastic material being recycled from waste plastic material originating from post-consumer waste and / or post-industrial waste, having a melt flow rate MFR2 (230°C, 2.16 kg, measured according to ISO 1133) in the range of 16 to 50 g / 10 min, and preferably in the range of 18 to 40 g / 10 min, and

[0155] c) optionally further additives, where the sum of all constituents always amounts to 100% by weight.

[0156] Such a first polyolefin composition may have the following

[0157] - a melt flow rate MFR2 (230° C., 2.16 kg, measured according to ISO 1133) in the range of 30 to 35 g / 10 min;

[0158] - tensile modulus (ISO 527-2) in the range of 1450 MPa to 1600 MPa, preferably 1460 MPa to 1500 MPa;

[0159] - Impact strength (Charpy 1eA+23℃) at 5.5kJ / m 2 Up to 7 kJ / m 2 , and most specifically 5.8 kJ / m 2 Up to 6.5 kJ / m 2 within the range.

[0160] In a second embodiment, a polyolefin composition is provided comprising:

[0161] a) 35 to 65 wt.-% (based on the total weight of the polyolefin composition) of at least one heterophasic polypropylene copolymer (PPHECO-1) having a total ethylene C2 content of 6 to 15 wt.-%, an ethylene content of the soluble fraction C2 (SF) of 30 to 35 wt.-% and a melt flow rate MFR2 (230°C, 2.16 kg, measured according to ISO 1133) in the range of 70 to 90 g / 10 min, preferably 72 to 88 g / 10 min;

[0162] b) 35 to 65 wt.-% (based on the total weight of the polyolefin composition) of a blend of recycled plastic material comprising polypropylene and polyethylene in a ratio of 3:7 to 49.5:1, said blend of recycled plastic material being recycled from waste plastic material originating from post-consumer waste and / or post-industrial waste, having a melt flow rate MFR2 (230°C, 2.16 kg, measured according to ISO 1133) in the range of 16 to 50 g / 10 min, and preferably in the range of 18 to 40 g / 10 min, and

[0163] c) optionally further additives, where the sum of all constituents always amounts to 100% by weight.

[0164] Such a second polyolefin composition may have the following:

[0165] - melt flow rate MFR2 (230° C., 2.16 kg, measured according to ISO 1133) in the range of 25 g / 10 min to 36 g / 10 min; preferably in the range of 30 g / 10 min to 35 g / 10 min;

[0166] - tensile modulus (ISO 527-2) in the range of 1450 MPa to 1600 MPa, preferably 1460 MPa to 1500 MPa;

[0167] - Impact strength (Charpy 1eA+23℃) at 5.5kJ / m 2 Up to 7 kJ / m 2 , and most specifically 5.8 kJ / m 2 Up to 6.5 kJ / m 2 within the range.

[0168] additive

[0169] In another embodiment, the polyolefin composition may include other additives. Examples of additives used in the composition are pigments or dyes (e.g., carbon black), stabilizers (antioxidants), antacids and / or anti-UV agents, antistatic agents, nucleators, antiblocking agents, and utilization agents (e.g., processing aids). Preferred additives are carbon black, at least one antioxidant, and / or at least one UV stabilizer.

[0170] Typically, the amount of these additives ranges from 0 wt% to 5.0 wt%, preferably from 0.01 wt% to 3.0 wt%, more preferably from 0.01 wt% to 2.0 wt%, based on the weight of the total composition.

[0171] Examples of antioxidants commonly used in the art are sterically hindered phenols (e.g. CAS No. 6683-19-8, also known as Irganox 1010FF TM sold by BASF), phosphorus-based antioxidants (e.g. CAS No. 31570-04-4, also as Hostanox PAR 24 (FF) TM Sold by Clariant or as Irgafos 168 (FF) TM Sold by BASF), sulfur-based antioxidants (e.g., CAS No. 693-36-7, as Irganox PS-802FL TM Sold by BASF), nitrogen-based antioxidants (e.g. 4,4'-bis(1,1'-dimethylbenzyl)diphenylamine), or antioxidant blends. Preferred antioxidants may be tris(2,4-di-tert-butylphenyl)phosphite and / or octadecyl 3-(3',5'-di-tert-butyl-4-hydroxyphenyl)propionate.

[0172] Antacids are also well known in the art. Examples are calcium stearate, sodium stearate, zinc stearate, magnesium oxide and zinc oxide, synthetic hydrotalcite (e.g. SHT, CAS No. 11097-59-9), lactates and lactyl esters, and calcium stearate (CAS No. 1592-23-0) and zinc stearate (CAS No. 557-05-1).

[0173] Common anti-adhesion agents are natural silicon dioxide, such as diatomaceous earth (e.g., CAS No. 60676-86-0 (SuperfFloss TM ), CAS number 60676-86-0 (SuperFloss E TM ), or CAS No. 60676-86-0 (Celite499 TM)); synthetic silica (e.g., CAS No. 7631-86-9, CAS No. 7631-86-9, CAS No. 7631-86-9, CAS No. 7631-86-9, CAS No. 7631-86-9, CAS No. 7631-86-9, CAS No. 112926-00-8, CAS No. 7631-86-9, or CAS No. 7631-86-9); silicates (e.g., aluminum silicate (kaolin )CAS No. 1318-74-7, sodium aluminum silicate CAS No. 1344-00-9, calcined kaolin CAS No. 92704-41-1, aluminum silicate CAS No. 1327-36-2, or calcium silicate CAS No. 1344-95-2); synthetic zeolite (e.g., sodium calcium aluminosilicate hydrate CAS No. 1344-01-0, CAS No. 1344-01-0, or sodium calcium aluminosilicate hydrate CAS No. 1344-01-0).

[0174] The anti-UV agent is, for example, bis(2,2,6,6-tetramethyl-4-piperidinyl)-sebacate (CAS No. 52829-07-9, Tinuvin 770); 2-hydroxy-4-n-octyloxy-benzophenone (CAS No. 1843-05-6, Chimassorb 81). Preferred UV stabilizers can be low molecular weight UV stabilizers and / or high molecular weight UV stabilizers, such as n-hexadecyl-3,5-di-tert-butyl-4-hydroxybenzoate, a mixture of esters of 2,2,6,6-tetramethyl-4-piperidinol and higher fatty acids (mainly stearic acid), and / or poly((6-morpholino-s-triazine-2,4-diyl)(1,2,2,6,6-pentamethyl-4-piperidinyl)imino)hexamethylene(1,2,2,6,6-pentamethyl-4-piperidinyl)imino)).

[0175] Alpha nucleating agents such as sodium benzoate (CAS No. 532-32-1); 1,3:2,4-bis(3,4-dimethylbenzylidene)sorbitol (CAS 135861-56-2, Millad 3988). Suitable antistatic agents are, for example, glycerol esters (CAS No. 97593-29-8) or ethoxylated amines (CAS No. 71786-60-2 or CAS No. 61791-31-9) or ethoxylated amides (CAS No. 204-393-1). For each individual component of the polymer, these additives are usually added in an amount of 100 ppm to 2.000 ppm.

[0176] The polyolefin composition according to the present invention can be used in a wide range of applications, for example for the manufacture of covers, closures, lids, thin-walled packaging.

[0177] method

[0178] As previously stated the polyolefin composition according to the present invention is obtained by extruding a blend of at least one heterophasic polypropylene copolymer and recycled plastic material in the presence of at least one peroxide.

[0179] Thus, the process for preparing a polyolefin composition as previously described comprises the following steps:

[0180] -supply

[0181] a) 35 to 65 wt.-% (based on the total weight of the polyolefin composition) of at least one heterophasic polypropylene copolymer having a melt flow rate MFR2 (230°C, 2.16 kg, measured according to ISO 1133) of at least 40 g / 10 min; and

[0182] b) 35 to 65 wt.-% (based on the total weight of the polyolefin composition) of a blend of recycled plastic material comprising polypropylene and polyethylene in a ratio of 3:7 to 49.5:1, said blend of recycled plastic material being recycled from waste plastic material originating from post-consumer waste and / or post-industrial waste,

[0183] - feeding / dosing the blend of at least one heterophasic polypropylene copolymer and recycled plastic material into at least one extruder individually or as a mixture,

[0184] - melting the mixture in at least one extruder,

[0185] - adding at least one peroxide to the molten mixture in said at least one extruder, and

[0186] - Optionally pelletizing the polyolefin composition obtained.

[0187] In one embodiment of the process of the present invention the blend of at least one heterophasic polypropylene copolymer and recycled plastic material is provided in the form of pellets or as flakes.

[0188] Therefore, in one embodiment of the process of the present invention, all polymer components, i.e. virgin heterophasic polypropylene copolymer and recyclate are provided as pellets and can be dosed separately in an extruder / compounder. In another embodiment, the pellets of the polymer components are premixed and can be dosed in an extruder / compounder as a mixture.

[0189] In one embodiment, a setup of a first extruder and a second extruder is used.

[0190] Therefore, according to a preferred embodiment of the method of the present invention,

[0191] - feeding the blend of recycled plastic materials into at least one first extruder, in particular a single screw extruder;

[0192] - melting the blend of recycled plastic materials in a first extruder and subsequently feeding the melt of the blend of recycled plastic materials into at least one second extruder,

[0193] - wherein at least one heterophasic polypropylene copolymer is dosed into the at least one second extruder, and

[0194] - wherein at least one peroxide is added to the molten mixture of recycled plastic material and the heterophasic polypropylene copolymer in the second extruder.

[0195] In an even more preferred embodiment of the process of the present invention, the recycled plastic material flakes are dosed into a combination of a single-screw extruder and a twin-screw extruder, wherein in the single-screw extruder the recycled plastic material flakes are purified, melted and optionally provided with additives, and subsequently the melt of the recycled plastic material is fed into a second twin-screw extruder, wherein to the melt of the recycled plastic material are added at least one heterophasic polypropylene copolymer and at least one peroxide.

[0196] Thus, the recyclate flakes undergo treatment steps (purification by filtration, degassing, additives) in an extruder (single screw extruder) and are finally pelletized. The recyclate pellets are then fed alone or together with a heterophasic polypropylene copolymer into a twin screw extruder / compounder where they undergo a (second) melting process in the presence of at least one peroxide.

[0197] The process of the invention allows for a targeted adjustment of the physical and mechanical properties of the final polyolefin composition. In particular, by adding at least one peroxide to the second extruder, it is now possible to adjust the melt flow rate as well as the impact strength and tensile modulus.

[0198] By adding at least one peroxide in the second extruder, thereby adding in the mixture of molten recycled plastic material and molten heterophasic polypropylene copolymer, at least one peroxide reacts with recycled plastic material and heterophasic polypropylene copolymer.In the process of this reaction, recycled plastic material and heterophasic polypropylene copolymer are both at least partially degraded.Therefore, the polyolefin composition obtained according to this method can also be described as a mixture of partially degraded recycled plastic material and heterophasic polypropylene copolymer.

[0199] In contrast, when the at least one peroxide is added only to the recycled plastic material in the first extruder, the at least one peroxide only at least partially degrades the recycled plastic material.The heterophasic polypropylene copolymer added to the second extruder is not degraded.

[0200] It is to be noted that the at least one peroxide is dosed into the molten mixture of recycled plastic material and heterophasic polypropylene copolymer in the second extruder during the extrusion process at a temperature allowing complete degradation of said at least one peroxide.

[0201] It should be noted that screw speed, melt temperature and residence time of the polymer in the extruder are strongly dependent on the size of the extruder (eg, ab scale or production scale extruder).

[0202] The at least one peroxide added during the course of the extrusion process is one of the following: 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane (commercially available under the trade names Trigonox 101, Luperox 101, Iniper 101 or Peroxan HX).

[0203] At least one peroxide may be added to the extruder in an amount of at least 0.5 wt%, preferably at least 0.8 wt%, even more preferably at least 1.0 wt% (based on the total weight of the polyolefin composition), for example in the range of 0.5 to 2.0 wt%, preferably 0.8 to 1.5 wt%, more preferably 0.9 to 1.2 wt%.

[0204] Experimental Section

[0205] The following examples are included to illustrate certain aspects and embodiments of the present invention as described in the claims. However, those skilled in the art will appreciate that the following description is illustrative only and should not be construed in any way as limiting the present invention.

[0206] Test Method

[0207] Unless otherwise defined, the following definitions of terms and methods apply to the above general description of the invention as well as the following examples.

[0208] a) Determination of the content of isotactic polypropylene (iPP), polystyrene (PS), ethylene, PVC and polyamide-6 in recycled material blends

[0209] Sample preparation

[0210] All calibration samples and samples to be analyzed were prepared in a similar manner on a melt-pressed plate. About 2 g to 3 g of the compound to be analyzed was melted at 190 ° C. Subsequently, a pressure of 60 to 80 bar was applied in a hydraulic heating press for 20 seconds. Next, the sample was cooled to room temperature within 40 seconds in a cold press at the same pressure to control the morphology of the compound. The thickness of the plate was controlled to be 100 μm to 200 μm thick (depending on the MFR from the sample) by a 2.5 cm × 2.5 cm metal calibration frame plate; two plates were produced in parallel at the same time and under the same conditions. The thickness of each plate was measured before any FTIR measurement; all plates were 100 μm to 200 μm thick. In order to control the plate surface and avoid any interference during the measurement, all plates were pressed between two double-sided silicone release papers. In the case of powder samples or inhomogeneous compounds, the pressing process was repeated three times to improve uniformity by pressing and cutting the sample under the same conditions as described above.

[0211] Spectrometer:

[0212] Use a standard transmission FTIR spectrometer such as a Bruker Vertex 70 FTIR spectrometer with the following settings:

[0213] 4000cm -1 Up to 400cm -1 The spectral range,

[0214] 6mm aperture,

[0215] 2cm -1 The spectral resolution,

[0216] 16 background scans, 16 spectrum scans,

[0217] An interference pattern zero filling factor of 32,

[0218] ·Norton Beer strong change.

[0219] Spectra were recorded and analyzed in Bruker Opus software.

[0220] Calibration samples:

[0221] Since FTIR is an indirect method, several calibration standards are composited to cover the analytical range of interest, typically:

[0222] ● For PA, 0.2 wt% to 2.5 wt%

[0223] ● For PS, 0.1 wt% to 5 wt%

[0224] For PET, 0.2 wt% to 2.5 wt%

[0225] ●For PVC, 0.1 wt% to 4 wt%

[0226] For the compounds, the following commercial materials were used: Borealis HC600TF as iPP, Borealis FB3450 as HDPE, and for the target polymers, for example, RAMAPET N1S (Indorama Polymer) for PET and B36LN (BASF), Styrolution PS 486N (Ineos) was used for High Impact Polystyrene (HIPS), and InovynPVC 263B (in powder form) was used for PVC.

[0227] All compounds were prepared on a small scale in a Haake kneader at temperatures below 265°C and less than 10 minutes to avoid degradation. Additional antioxidants such as Irgafos 168 (3000 ppm) were added to minimize degradation.

[0228] calibration:

[0229] The FTIR calibration principle is the same for all components: the intensity of a specific FTIR band divided by the plate thickness is 1 H or 13 C solution state NMR correlates with the amounts of components determined on the same plate.

[0230] Each specific FTIR absorption band was chosen because its intensity increases with the amount of component concentration and because it is separated from the remaining peaks, regardless of the composition of the calibration standards and actual samples.

[0231] The methodology is described in the publication from Signoret et al. “Alterations of plastic spectrain MIR and the potential impacts on identification towards recycling”, Resources, conservation and Recycling journal, 2020, Vol. 161, Article 104980.

[0232] The wavelengths of the calibration bands are:

[0233] ●For PA, 3300cm -1 ,

[0234] ●For PS, 1601cm -1 ,

[0235] ●For PET, 1410cm -1 ,

[0236] ●For PVC, 615cm -1 ,

[0237] For iPP, 1167cm -1 .

[0238] For each polymer component i, a linear calibration (linearity based on the Beer-Lambert law) is constructed. A typical linear correlation for such a calibration is given below:

[0239]

[0240] where x i is the fraction of polymer component i (in wt%)

[0241] E i is the absorbance intensity (in au absorbance units) of the specific bands associated with polymer component i. These specific bands are: for PA, 3300 cm -1 ; for PS, 1601cm -1 ; for PET, 1410cm -1 ; For PVC, 615cm -1 ; for iPP, 1167cm -1

[0242] d is the thickness of the sample plate

[0243] A i and B i are the two correlation coefficients determined for each calibration curve

[0244] For the C2-rich fraction, no specific separation band could be found, and thus the C2-rich fraction was estimated indirectly.

[0245] x 富C2 =100-(x iPP +x PA +x PS +x PET +x EVA +x PVC +x 白垩 +x 滑石 )

[0246] The EVA, chalk and talc contents were estimated "semi-quantitatively". This therefore makes the C2-rich content "semi-quantitative".

[0247] For each calibration standard, whenever available, the amount of each component is given by1 H or 13 C Solution state NMR was determined as the primary method (in addition to PA). NMR measurements were performed on the exact same FTIR plate used to construct the FTIR calibration curve.

[0248] Calibration standards were prepared by blending iPP and HDPE to form a calibration curve. The thickness of the film of the calibration standard was 300 μm. To quantify the iPP, PS and PA6 content in the samples, quantitative IR spectra were recorded in the solid state using a Bruker Vertex 70 FTIR spectrometer. Spectra were recorded on 25×25 mm square films of 50 μm to 100 μm thickness prepared by compression molding at 190°C and 4 to 6 mPa. Standard transmission FTIR spectroscopy was employed using: 4000 cm -1 Up to 400cm -1 spectral range, 6mm aperture, 2cm -1 spectral resolution, 16 background scans, 16 spectral scans, interferogram zero fill factor of 32, and Norton Beer strong apodization.

[0249] Measure iPP at 1167cm -1 The absorbance of the band at 100 Å was measured and the iPP content was quantified according to a calibration curve (absorption / thickness (in cm) vs. iPP content (in wt %)).

[0250] Measurements 1601cm -1 (PS) and 3300cm -1 The absorbance of the band at (PA6) was measured and the PS and PA6 contents were quantified according to a calibration curve (absorption / thickness in cm vs. PS and PA content in wt%). The ethylene content was obtained by subtracting the iPP, PS and PA6 contents from 100. The analysis was performed as a duplicate determination.

[0251] b) The amount of talc and chalk in the recyclate blend was measured by thermogravimetric analysis (TGA); the experiment was performed with a PerkinElmer TGA8000. About 10 mg to 20 mg of material was placed in a platinum pan. The temperature was equilibrated at 50°C for 10 minutes, after which it was raised to 950°C at a heating rate of 20°C / min under nitrogen. The weight loss (WCO2) from about 550°C to 700°C was assigned to CO2 released from CaCO3, and the chalk content was therefore estimated as:

[0252] Chalk content = 100 / 44×WCO2

[0253] Afterwards, the temperature was lowered to 300°C at a cooling rate of 20°C / min. The gas was then switched to oxygen and the temperature was raised again to 900°C. The weight loss in this step was designated as carbon black (Wcb). Knowing the contents of carbon black and chalk, the ash content excluding chalk and carbon black was calculated as:

[0254] Ash content = (ash residue) - 56 / 44 × WCO2 - Wcb

[0255] The ash residue is in % by weight measured at 900° C. in a first step carried out under nitrogen. The ash content is estimated to be identical to the talc content of the recyclate studied.

[0256] c) Amount of paper and wood in the recycled content blend

[0257] Paper and wood are determined by conventional laboratory methods including grinding, flotation, microscopy and thermogravimetric analysis (TGA) or by flotation techniques where the polymer is dissolved followed by gravimetric determination of the paper and wood content.

[0258] d) The amount of metals in the recyclate blend was determined by x-ray fluorescence (XRF).

[0259] e) The amount of limonene in the recyclate blend was determined by solid phase microextraction (HS-SPME-GC-MS). Additional details are given below for specific samples.

[0260] f) The amount of total fatty acids in the recyclate blend was determined by solid phase microextraction (HS-SPME-GC-MS).Additional details are given below for specific samples.

[0261] g) Xylene Cold Soluble (XCS) in the recyclate blend is measured according to ISO 16152; First Edition; 2005-07-01 at 25°C.

[0262] h) Crystex analysis of recycled material blends

[0263] Crystalline fraction and soluble fraction method

[0264] The crystalline fraction (CF) and soluble fraction (SF) of the polypropylene (PP) composition as well as the comonomer content and intrinsic viscosity of each fraction were analyzed by CRYSTEX QC of Polymer Char (Valencia, Spain). The crystalline and amorphous fractions were separated by temperature cycles of dissolution at 160°C, crystallization at 40°C, and redissolution in 1,2,4-trichlorobenzene (1,2,4-TCB) at 160°C. The quantification of SF and CF as well as the determination of the ethylene content (C2) of the parent EP copolymer and its soluble and crystalline fractions were achieved by an infrared detector (IR4) and an online 2-capillary viscometer for determining the intrinsic viscosity (IV).

[0265] The IR4 detector is a multi-wavelength detector that detects IR absorbance at two different bands (CH3 and CH2) to determine the concentration and ethylene content in ethylene-propylene copolymers. The IR4 detector is calibrated with a series of 8 EP copolymers with known ethylene contents ranging from 2 wt% to 69 wt% (given by 13 C-NMR spectroscopy) and had various concentrations from 2 mg / ml to 13 mg / ml for the various EP copolymers used for calibration.

[0266] The amount of soluble fraction (SF) and crystalline fraction (CF) is related by XS calibration to the amount of "xylene cold soluble" (XCS) and the xylene cold insoluble (XCI) fraction, respectively, determined according to the standard gravimetric method according to ISO 16152. The XS calibration was achieved by testing various EP copolymers with XS contents ranging from 2 wt% to 31 wt%.

[0267] The intrinsic viscosity (iV) of the parent EP copolymer and its soluble and crystalline fractions was determined using an online 2-capillary viscometer and correlated to the corresponding iV determined by the standard method in decalin according to ISO 1628. Calibration was achieved with various EP PP copolymers ranging from iV = 2 dL / g to 4 dL / g.

[0268] The PP composition samples to be analyzed were weighed out at a concentration of 10 to 20 mg / ml. After automatically filling the vials with 1,2,4-TCB containing 250 mg / l of 2,6-tert-butyl-4-methylphenol (BHT) as an antioxidant, the samples were dissolved at 160°C with constant stirring at 800 rpm until complete dissolution was achieved (usually for 60 minutes).

[0269] A defined volume of sample solution is injected into a column filled with an inert support, where crystallization of the sample and separation of the soluble fraction from the crystalline part occur. This process is repeated twice. During the first injection, the entire sample is measured at high temperature, and the iV [dl / g] and C2 [wt%] of the PP composition are determined. During the second injection, the soluble fraction (at low temperature) and the crystalline fraction (at high temperature) are measured in the case of a crystallization cycle (wt% of SF, wt% of C2, iV).

[0270] EP means ethylene propylene copolymer.

[0271] PP means polypropylene.

[0272] i) Regio defects: quantification of microstructure by NMR spectroscopy

[0273] Quantitative nuclear magnetic resonance (NMR) spectroscopy was further used to quantify the comonomer content and comonomer sequence distribution of the polymers. A Bruker Advance III 400 NMR spectrometer was used at 400.15 MHz and 100.62 MHz, respectively. 1 H and 13 C to operate and record the quantity in solution state 13 C{ 1 H} NMR spectra. All spectra were obtained using 13C optimized 10mm extended temperature probe was recorded at 125°C, using nitrogen for all pneumatic devices. About 200mg of material was dissolved in 3ml 1,2-tetrachloroethane-d2 (TCE-d2) along with chromium (III) acetylacetonate (Cr(acac)3) to obtain a 65mM solution of the relaxant in the solvent (Singh, G., Kothari, A., Gupta, V., Polymer Testing 28 5 (2009), 475). To ensure a homogeneous solution, the NMR tube was further heated in a rotary oven for at least 1 hour after initial sample preparation in a heating block. After insertion into the magnet, the tube was rotated at 10Hz. This setup was chosen primarily for high resolution and the quantitation required for accurate quantification of ethylene content. Standard single pulse excitation without NOE was used, using optimized tip angle, 1 second recycle delay and double-stage WALTZ16 decoupling scheme (Zhou, Z., Kuemmerle, R., Qiu, X., Redwine, D., Cong, R., Taha, A., Baugh, D. Winniford, B., J. Mag. Reson. 187 (2007) 225; Busico, V., Carbonniere, P., Cipullo, R., Pellecchia, R., Severn, J., Talarico, G., Macromol. Rapid Commun. 2007, 28, 1128). A total of 6144 (6k) transients were obtained for each spectrum.

[0274] A proprietary computer program was used to quantify 13 C{ 1 H} NMR spectra are processed, integrated, and the relevant quantitative properties are determined from the integration. All chemical shifts are indirectly referenced to the central methylene of the ethylene block (EEE) at 30.00 ppm using the chemical shift of the solvent. This method allows for comparable reference even when this structural unit is not present. Characteristic signals corresponding to the incorporation of ethylene are observed (Cheng, HN, Macromolecules 17 (1984), 1950).

[0275] In the case where characteristic signals corresponding to 2,1 erythro regio defects are observed (as described in L. Resconi, L. Cavallo, A. Fait, F. Piemontesi, Chem. Rev. 2000, 100 (4), 1253, Cheng, HN, Macromolecules 1984, 17, 1950, and WJ Wang and S. Zhu, Macromolecules 2000, 33 1157), it is necessary to correct for the influence of the regio defects on the determined properties. Characteristic signals corresponding to other types of regio defects are not observed.

[0276] The method of Wang et al. (Wang, WJ., Zhu, S., Macromolecules 33 (2000), 1157) was used to 13 C{ 1 The comonomer fraction is quantified by integrating multiple signals over the entire spectral area in the H} spectrum. This method was chosen for its robust nature and ability to account for the presence of regio defects when required. The integration area is slightly adjusted to improve applicability to the entire range of comonomer contents encountered.

[0277] For systems where only isolated ethylene is observed in the PPEPP sequence, the method of Wang et al. is modified to reduce the effect of non-zero integrals at sites known to be absent. This method reduces the overestimation of ethylene content in such systems and is achieved by reducing the number of sites used to determine the absolute ethylene content by:

[0278] E=0.5(Sββ+Sβγ+Sβδ+0.5(Sαβ+Sαγ))

[0279] Using this set of sites, the corresponding integral equation becomes:

[0280] E=0.5(I H +I G +0.5(I C +I D ))

[0281] The same symbols are used as in the article by Wang et al. (Wang, WJ., Zhu, S., Macromolecules 33 (2000), 1157). The equations for absolute propylene content are not modified.

[0282] The comonomer incorporation mole percent is calculated from the mole fraction:

[0283] E[mol%]=100*fE

[0284] The comonomer incorporation weight percent is calculated from the mole fraction:

[0285] E[weight%]=100*(fE*28.06) / ((fE*28.06)+((1-fE)*42.08))

[0286] The comonomer sequence distribution at the ternary level was determined using the analytical method of Kakugo et al. (Kakugo, M., Naito, Y., Mizunuma, K., Miyatake, T. Macromolecules 15 (1982) 1150). This method was chosen because of its robust nature and slightly adjusted integration region to improve applicability to a wider range of comonomer content.

[0287] j) Melt flow rate is measured at 230°C (for polypropylene) or 190°C (for polyethylene) under a load of 2.16 kg (MFR2), as indicated. The melt flow rate is the amount of polymer in grams which a test apparatus standardized to ISO 1133 extrudes in 10 minutes at a temperature of 230°C (or 190°C) under a load of 2.16 kg.

[0288] k) Tensile modulus, tensile strength, tensile strain at break, tensile strain at tensile strength, tensile stress at break, flexural modulus

[0289] The test specimens were measured after a conditioning time of 96 hours (at 23° C. at 50% relative humidity).

[0290] Tensile modulus was measured according to ISO 527-2 (crosshead speed = 1 mm / min; 23°C) using injection molded test specimens (dog bone, 4 mm thickness) as described in EN ISO 1873-2.

[0291] Tensile strength and tensile strain at break were measured according to ISO 527-2 (crosshead speed = 50 mm / min; 23°C) using injection moulded test specimens (dog bone, 4 mm thickness) as described in EN ISO 1873-2.

[0292] The tensile strain under tensile strength is determined according to ISO 527-2 using injection molded test specimens as described in EN ISO 1873-2 (dog bone shape, 4 mm thickness) at an elongation rate of 50 mm / min until the specimen breaks.

[0293] The tensile stress at break was determined according to ISO 527-2 (cross head speed = 50 mm / min) on specimens prepared from compression molded plaques with a specimen thickness of 4 mm.

[0294] The flexural modulus is determined according to ISO 178 standard.

[0295] 1) Impact strength The Charpy impact strength was determined on injection-molded test specimens 80 mm×10 mm×4 mm prepared according to EN ISO 1873-2 according to ISO 179-1 / 1eA at +23° C. (notched) or according to ISO 179-1 / 1eU at +23° C. (unnotched). According to this standard, the specimens were tested after 96 hours.

[0296] In Table 1, several examples (Comparative Examples - CE; Inventive Examples - IE) are summarized.

[0297] Blend B1 (with 916 kg / m 3 The present invention relates to a polyurethane foam having a density of 100 g / 100 g (determined in accordance with DIN EN ISO 1183), a melt flow rate of 36 g / 10 min (determined in accordance with DIN EN ISO 1133 at 230°C / 2.16 kg), a moisture content of less than 0.1% (determined via a moisture infrared analyzer at 105°C), a tensile modulus of greater than 1100 MPa (determined in accordance with DIN EN ISO 527 at 1 mm / min), a yield stress of greater than 24 MPa (determined in accordance with DIN EN ISO 527 at 50 mm / min) and a tensile strain of greater than 18% (determined in accordance with DIN EN ISO 527 at 50 mm / min).

[0298] The comparative and inventive compositions were subjected to the same process steps and conditions.

[0299] The flakes of recyclate blend B1 were dosed into a combination of single and twin screw extruders, wherein the recycled plastic material flakes were purified, melted in the single screw extruder, and then the melt of recycled plastic material was subsequently fed into a second extruder, wherein PPHECO-2 and peroxide were added to the melt of recycled plastic material.

[0300] Table 1 relates to a polyolefin composition comprising:

[0301] - Comparative example (CE1): blend of recycled materials (Blend B1) without addition of peroxide;

[0302] - Comparative Example (CE2): Blend of recycled material (Blend B1) and a heterophasic polypropylene copolymer (PPHeco-2, MFR2 70 g / 10 min, T c =112.3°C); no peroxide is added during the extrusion process;

[0303] - Inventive example (IE1): Blend of recycled material (Blend B1) and a heterophasic polypropylene copolymer (PPHeco-2, MFR2 70 g / 10 min, T c =112.3°C); peroxide (=POX, 2,5-dimethyl-2,5-di-(tert-butylperoxy)hexane as MB, peroxide content 1%) was added during extrusion.

[0304] Manufacturing of PPHeco-2

[0305] Catalyst preparation

[0306] raw material

[0307] TiCl4 (CAS 7550-45-90) was provided by a commercial source.

[0308] 20% butylethylmagnesium (Mg(Bu)(Et)) in toluene, supplied by Crompton

[0309] 2-Ethylhexanol, supplied by Merck Chemicals

[0310] 3-Butoxy-2-propanol, supplied by Sigma-Aldrich

[0311] Bis(2-ethylhexyl) citrate, supplied by Contract Chemicals

[0312] 1-254, provided by Evonik

[0313] Heptane, supplied by Chevron

[0314] Preparation of Mg complexes

[0315] 3.4 l of 2-ethylhexanol and 810 ml of propylene glycol monobutyl ether (in a 4 / 1 molar ratio) were added to a 20 l reactor. Then 7.8 l of a 20% toluene solution of BEM (butylethylmagnesium) supplied by Crompton GmbH was slowly added to the well-stirred alcohol mixture. During the addition, the temperature was maintained at 10 ° C. After the addition, the temperature of the reaction mixture was raised to 60 ° C and mixing was continued at this temperature for 30 minutes. Finally, after cooling to room temperature, the obtained Mg-alkoxide was transferred to a storage container.

[0316] 21.2 g of the Mg alkoxide prepared above was mixed with 4.0 ml of bis(2-ethylhexyl) citrate for 5 minutes. After mixing, the obtained Mg complex was immediately used for the preparation of the catalyst component.

[0317] Preparation of catalyst components

[0318] 19.5 ml of titanium tetrachloride were placed in a 300 ml reactor equipped with a mechanical stirrer at 25°C. The mixing speed was adjusted to 170 rpm. The temperature was maintained at 25°C and 26.0 of the Mg-complex prepared above were added over 30 minutes. 3.0 ml of Viscoplex 1-254 and 24.0 ml of heptane were added to form an emulsion. Mixing was continued at 25°C for 30 minutes. The reactor temperature was then raised to 90°C over 30 minutes. The reaction mixture was stirred at 90°C for an additional 30 minutes. Thereafter, stirring was stopped and the reaction mixture was allowed to stand at 90°C for 15 minutes.

[0319] The solid material was washed with 100 ml toluene, 30 ml TiCl4, 100 ml toluene and twice with 60 ml heptane. 1 ml of donor D was added to the first two washes. The washes were performed with stirring at 170 rpm for 30 minutes at 80°C. After stopping the stirring, the reaction mixture was allowed to stand for 20 to 30 minutes and then siphoned.

[0320] Thereafter, stirring was stopped and the reaction mixture was allowed to stand for 10 minutes to lower the temperature to 70° C. and then siphon, and then N 2 purged for 20 minutes to produce an air-sensitive powder.

[0321] The surface area of ​​the catalyst measured by the BET method is less than 5 m 2 / g, which is below the detection limit.

[0322] polymerization:

[0323] Borstar pilot plant with a 4-reactor setup (loop reactors - GPR1 - GPR2 - GPR3) and a prepolymerization loop reactor.

[0324] Table 1: Polymerization conditions of PPHeco-2

[0325] Prepolymerization reactor temperature ℃ 30 Dwell time Hour 0.37 Loop Reactor temperature ℃ 80 pressure kPa 53 H2 / C3 Ratio mol / kmol 25.4 Polymer splitting weight% 40 Polymer residence time Hour 0.25 <![CDATA[MFR2]]> g / 10 minutes 310 Gas phase reactor 1 temperature ℃ 80 pressure kPa 2100 H2 / C3 Ratio mol / kmol 203 Polymer splitting weight% 38 Polymer residence time Hour 1.70 <![CDATA[MFR2]]> g / 10 minutes 339 <![CDATA[MFR2 (Calculation) in GPR1]]> g / 10 minutes 210 Gas phase reactor 2 temperature ℃ 80 pressure kPa 27 H2 / C2 Ratio mol / kmol 147.3 C2 / C3 Ratio mol / kmol 0 Polymer splitting weight% 40 Polymer residence time Hour 3.1 Gas phase reactor 3 temperature ℃ 75 pressure kPa 25 H2 / C2 Ratio mol / kmol 158.8 C2 / C3 Ratio mol / kmol 401.6 Polymer splitting weight% 20 Polymer residence time Hour 1.2

[0326] The following additives were used: antioxidants: AO1 (Irganox 1010 (FF)), AO2 (Irganox B 225 (FF)), AO3 (Irganox PS-802FL); AO4 (AO501GRA), white pigment (MB90-white 6-PE-70 35%); dosing agent: HC001A-B1,

[0327] Table 2: Polymer composition and properties.

[0328] Material unit CE1 CE2 IE1 Blend B1 weight% 98.7 48.7 48.7 PPHeco-2 weight% 50 50 Dosing agent weight% 1 1 1 Antioxidant AO4 (AO501GRA) weight% 0.3 0.3 0.3 POX (1 wt % based on the weight of the composition) weight% no no yes <![CDATA[MFR2 230℃ / 2.16kg]]> g / 10 minutes 37 43.3 35 Tensile modulus 23℃ MPa 1308 1451 1484 Impact strength 1eA+23℃ kJ / m2 5.4 4.8 5.8

[0329] As can be seen in Table 1, the tensile modulus and impact strength of the heterophasic copolymer recyclate composition according to Inventive Example IE 1 are higher than one of the recyclate composition CE1 and the heterophasic copolymer-recyclate composition CE2. At the same time, the melt flow rates are comparable.

[0330] Thus, the properties of the heterophasic copolymer-recyclate composition according to the invention are characterized by impact strength and tensile modulus indicating that the material is stable.

Claims

1. A polyolefin composition comprising: a) 35 to 65 wt.-% (based on the total weight of the polyolefin composition) of at least one heterophasic polypropylene copolymer having a total ethylene C2 content of 6 to 15 wt.-%, an ethylene content of the soluble fraction C2 (SF) content of 25 to 40 wt.-% and a melt flow rate MFR2 (230°C, 2.16 kg, measured according to ISO 1133) in the range of 60 to 90 g / 10 min; and b) 35 to 65 wt.-% (based on the total weight of the polyolefin composition) of a blend of recycled plastic material comprising polypropylene and polyethylene in a ratio of 3:7 to 49.5:1, said blend of recycled plastic material being recycled from waste plastic material originating from post-consumer waste and / or post-industrial waste, c) optionally further additives, where the sum of all constituents always amounts to 100% by weight, The polyolefin composition is characterized by - Impact strength (ISO179-1, Charpy 1eA+23℃) is 5kJ / m 2 Up to 8kJ / m 2 , - a melt flow rate MFR2 (230° C., 2.16 kg, measured according to ISO 1133) of 30 to 80 g / 10 min, and - Tensile modulus (Iso 527-2) in the range of 1450 MPa to 1600 MPa.

2. The polyolefin composition according to claim 1, characterized in that the polyolefin composition comprises: a) 40 to 60 wt.-%, preferably 45 to 55 wt.-%, more preferably 48 to 52 wt.-% (based on the total weight of the polyolefin composition) of said at least one heterophasic polypropylene copolymer; b) 40 to 60 wt.-%, preferably 45 to 55 wt.-%, preferably 48 to 52 wt.-% (based on the total weight of said polyolefin composition) of a blend of said recycled plastic material comprising polypropylene and polyethylene, and optionally further additives, wherein the sum of all constituents always amounts to 100% by weight.

3. The polyolefin composition according to claim 1, characterized in that the impact strength (ISO 179, Charpy 1eA + 23°C) is 5.2 kJ / m 2 Up to 7.5 kJ / m 2 , especially 5.5 kJ / m 2 Up to 7 kJ / m 2 , and more specifically 5.8 kJ / m 2 Up to 6.5 kJ / m 2 .

4. The polyolefin composition according to claim 1 , characterized in that the melt flow rate MFR2 (230° C., 2.16 kg, measured according to ISO 1133-1) is in the range of 30 to 75 g / 10 min, more preferably 35 to 70 g / 10 min, or 30 to 36 g / 10 min.

5. Polyolefin composition according to one of the preceding claims, characterised in that the tensile modulus (ISO 527-2) is from 1450 MPa to 1550 MPa, preferably from 1450 MPa to 1500 MPa, more preferably from 1460 MPa to 1500 MPa.

6. Polyolefin composition according to one of the preceding claims, characterised in that the at least one heterophasic polypropylene copolymer a) is selected from the group comprising: at least one heterophasic polypropylene copolymer (PPHeco-1) having a melt flow rate MFR2 (230°C, 2.16 kg, measured according to ISO 1133) in the range of 60 to 90 g / 10 min, preferably 70 to 90 g / 10 min, more preferably 72 to 88 g / 10 min; At least one heterophasic polypropylene copolymer (PPHeco-2) having a melt flow rate MFR2 (230°C, 2.16 kg, measured according to ISO 1133) in the range of 60 to 90 g / 10 min, more preferably 65 to 80 g / 10 min, more preferably 65 to 75 g / 10 min; or a mixture thereof.

7. The polyolefin composition according to one of the preceding claims, characterised in that the blend of recycled plastic material comprising polypropylene and polyethylene has a melt flow rate MFR2 (230°C, 2.16 kg, measured according to ISO 1133) of at least 5 g / 10 min, preferably at least 10 g / 10 min, more preferably at least 15 g / 10 min, in particular in the range of 5 g / 10 min to 50 g / 10 min, preferably 10 g / 10 min to 45 g / 10 min, more preferably 15 g / 10 min to 40 g / 10 min.

8. Polyolefin composition according to one of the preceding claims, characterised in that the blend of recycled plastic materials comprises units derived from propylene in a relative amount of more than 50 wt.-%, preferably more than 53 wt.-%, more preferably more than 60 wt.-%, more preferably more than 70 wt.-%, more preferably more than 75 wt.-%, more preferably more than 80 wt.-%, yet more preferably more than 90 wt.-% and even more preferably more than 95 wt.-%, relative to the total weight of the blend of recycled plastic materials.

9. The polyolefin composition according to one of the preceding claims, characterized in that the blend of recycled plastic materials comprises units derived from ethylene in a relative amount of less than 47 wt.-%, more preferably less than 40 wt.-%, more preferably less than 30 wt.-%, more preferably less than 20 wt.-%, most preferably less than 10 wt.-%, relative to the total weight of the blend of recycled plastic materials.

10. Polyolefin composition according to one of the preceding claims, characterized in that the polyolefin composition is obtained by extruding a blend of the at least one heterophasic polypropylene copolymer and the recycled plastic material in the presence of at least one peroxide.

11. A process for the preparation of a polyolefin composition according to one of the preceding claims, comprising the steps of: -supply a) 35 to 65 wt.-% (based on the total weight of the polyolefin composition) of at least one heterophasic polypropylene copolymer having a melt flow rate MFR2 (230°C, 2.16 kg, measured according to ISO 1133) in the range of 60 to 90 g / 10 min; and b) 35 to 65 wt.-% (based on the total weight of the polyolefin composition) of a blend of recycled plastic material comprising polypropylene and polyethylene in a ratio of 3:7 to 49.5:1, said blend of recycled plastic material being recycled from waste plastic material originating from post-consumer waste and / or post-industrial waste, - feeding / dosing the blend of said at least one heterophasic polypropylene copolymer and said recycled plastic material into at least one extruder individually or as a mixture, - melting said mixture in said at least one extruder, - adding at least one peroxide to the molten mixture in said at least one extruder, and - Optionally pelletizing the polyolefin composition obtained.

12. The method according to claim 11, characterized in that the blend of recycled plastic materials is fed into at least one first extruder, in particular a single screw extruder, the blend of recycled plastic materials is melted in the first extruder and the melt is subsequently fed into at least one second extruder, wherein at least one heterophasic polypropylene copolymer is dosed into the at least one second extruder and the at least one peroxide is added to the molten mixture of the recycled plastic material and the heterophasic copolymer in the second extruder.

13. The method according to one of claims 11 to 12, characterized in that the recycled plastic material flakes are dosed into a combination of a single screw extruder and a twin screw extruder, wherein in the single screw extruder the recycled plastic material flakes are purified, melted and optionally provided with additives, and subsequently the melt of recycled plastic material is fed into a second twin screw extruder, wherein the at least one heterophasic polypropylene copolymer and the at least one peroxide are added to the melt of recycled plastic material.

14. Use of the polyolefin composition according to one of claims 1 to 10 for the manufacture of appliances, in particular household appliances.

15. An article comprising the polyolefin composition according to one of claims 1 to 10.

Citation Information

Patent Citations

  • Derivatized alkylpolysilane preceramic polymers

    CA1318747C

  • Substituted phenols as stabilizers for chlorinated polymers

    CA2043931A1

  • Heat sealable blend of very low density polyethylene or plastomer with polypropylene based polymers and heat sealable film and articles made thereof

    EP0575465B1

  • Polypropylene-polyethylene composition with improved flowability

    EP3165473A1

  • Plastomer compatibilized polyethylene / polypropylene blends

    US5266392A